Physical Activity and Psychological Well-Being During the COVID-19 Lockdown: Relationships With Motivational Quality and Nature Contexts - Matthew Jenkins; Susan Houge Mackenzie; Ken Hodge; Elaine Anne Hargreaves; Jessica R. Calverley; Craig Lee (Frontiers Media S.A., 2021)
The COVID-19 pandemic is a global event that has already had substantive negative impacts on psychological well-being. This study investigated the relationship between physical activity (PA) and psychological well-being during a country-wide COVID-19 lockdown in New Zealand. Motivational quality and PA context (nature-based or non-nature-based) were included as potential mediating and moderating variables within this relationship, respectively. Participants completed an online survey assessing psychological well-being, weekly PA levels, and PA during the second and third weeks of the 7 week COVID-19 lockdown period in New Zealand. Data were analysed using Partial Least Squares Structural Equation Modelling. Results showed that PA significantly predicted psychological well-being, with no significant difference evident in psychological well-being dependent on whether PA was nature or non-nature-based. Nature-based PA was a stronger predictor of intrinsic motivation compared to non-nature-based PA, and intrinsic motivation was positively associated with psychological well-being. In contrast, non-nature-based PA was a stronger predictor of introjected regulation compared to nature-based PA, which was negatively associated with psychological well-being. Overall, these findings suggest that (1) weekly PA was associated with increased psychological well-being during the lockdown, and (2) nature-based PA may foster psychological well-being via effects on motivation. The implications for continued participation in PA will be discussed.